2013
DOI: 10.1007/s12026-013-8459-y
|View full text |Cite
|
Sign up to set email alerts
|

CHI3L1 plays a role in cancer through enhanced production of pro-inflammatory/pro-tumorigenic and angiogenic factors

Abstract: Elevated serum levels of a glycoprotein known as chitinase-3-like protein 1 (CHI3L1) have been correlated with poor prognosis and shorter survival of patients with cancer and inflammatory diseases. The biological and physiological functions of CHI3L1 in cancer have not yet been completely elucidated. In this review, we describe the role of CHI3L1 in inducing pro-inflammatory/pro-tumorigenic and angiogenic factors that could promote tumor growth and metastasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
92
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 91 publications
(96 citation statements)
references
References 79 publications
1
92
0
Order By: Relevance
“…The most prominent cytokine/chemokine detected in the SCLC CTC supernatants CHI3L1 is also known as YKL-40 (86). CH3L1 pseudo-chitinase, which exhibits an inactivated enzymatic site but has retained chitin-binding activity, functions as regulatory factor of normal cell types, including macrophages (106). CHI3L1/YKL-40 has been described as soluble marker of invasive cancers with poor prognosis for a wide range of malignancies including lung cancer and, particularly, SCLC.…”
Section: Chi3l1 In Inflammation and Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…The most prominent cytokine/chemokine detected in the SCLC CTC supernatants CHI3L1 is also known as YKL-40 (86). CH3L1 pseudo-chitinase, which exhibits an inactivated enzymatic site but has retained chitin-binding activity, functions as regulatory factor of normal cell types, including macrophages (106). CHI3L1/YKL-40 has been described as soluble marker of invasive cancers with poor prognosis for a wide range of malignancies including lung cancer and, particularly, SCLC.…”
Section: Chi3l1 In Inflammation and Cancermentioning
confidence: 99%
“…Lung metastasis of melanoma and breast cancer cells was reduced after blocking ChI3L1 with antibodies or removing its regulator semaphorin 7a in experimental animals (98). Treatment with chitin microparticles inhibited tumor growth and angiogenesis at primary tumor sites but also reduced metastasis to the lung (106,111). CHI3L1 was also shown to bind the surface "Receptor for Advance Glycation End" Product (RAGE) which supports progression of solid tumors through promotion cell proliferation, migration and survival (112).…”
Section: Chi3l1 In Inflammation and Cancermentioning
confidence: 99%
“…In assessing the clinical significance of MMPs, such as MMP-9 in melanoma patients, Lugowska et al [15] found that serum concentrations of VEGF, MMP-2 and -9, and YKL-40/CHI3L1 were significantly higher in melanoma patients compared with the control group. YKL-40/CHI3L1 was one of the tumor-and host-derived factors that induced the expression of MMP-9 by macrophages [16,17].…”
Section: Tumor-associated Inflammationmentioning
confidence: 99%
“…TAMs contribute to tumor growth and metastasis by secreting MMPs that promote extracellular matrix remodeling; angiogenic factors that increase blood vessel formation; and cytokines, chemokines, and growth factors that enhance tumor growth [18,19]. Specifically, TAMs have been reported to produce VEGF, epidermal growth factor, basic fibroblast growth factor, platelet-derived growth factor, IL-6, MCP-1, CXCL18, CXCL12, and YKL-40/CHI3L1 [16,[20][21][22][23][24][25]. YKL-40/CHI3L1 induces the expression of MCP-1/CCL2 and IL-8/CXCL2, which are chemoattractants for monocytes/ macrophages and neutrophils [16].…”
Section: Tumor-associated Inflammationmentioning
confidence: 99%
See 1 more Smart Citation